1986
DOI: 10.1111/j.1432-1033.1986.tb10441.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4-phosphate kinase from rat brain. Activation by polyamines and inhibition by phosphatidylinositol 4,5-bisphosphate

Abstract: Phosphatidylinositol-4-phosphate (PtdIns-P) kinase was purified approximately 30-fold from rat brain cytosol. No contaminating activity of PtdIns kinase or of phosphomonoesterase and phospholipase C using PtdIns-P or PtdIns-P2 as substrate could be detected in the enzyme preparation. The PtdIns-P kinase activity was severalfold higher when PtdIns-PIPtdEtn vesicles rather than PtdIns-P alone were used as substrate. This might be due to increased accessibility of the enzyme for the vesicular substrate, further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The 2 best-characterized cytosolic effects of spermidine and spermine that are not shared by putrescine are inward rectification of inwardly rectifying potassium (Kir) channels (49,50) and dramatic enhancement of PIP5K1γ activity (31,51). We have previously shown that integrin α 9 β 1 -mediated enhancement of cell migration is caused by altered rectification of a specific Kir channel, Kir4.2 (25), and have found that Kir4.2 is also the major Kir channel expressed in airway smooth muscle (our unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The 2 best-characterized cytosolic effects of spermidine and spermine that are not shared by putrescine are inward rectification of inwardly rectifying potassium (Kir) channels (49,50) and dramatic enhancement of PIP5K1γ activity (31,51). We have previously shown that integrin α 9 β 1 -mediated enhancement of cell migration is caused by altered rectification of a specific Kir channel, Kir4.2 (25), and have found that Kir4.2 is also the major Kir channel expressed in airway smooth muscle (our unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy are unknown, but here again caution should be exercised since several types of this kinase can occur in a tissue (see, e.g., Endemann et al, 1987). The formation of Ptdlns(4,5)P2, catalysed by the Ptdlns(4)P 5-kinase, is also activated several-fold by polyamines in rat brain or liver plasma membranes (Lundberg et al, 1986(Lundberg et al, , 1987. Interestingly, work with a partially purified rat brain kinase indicated that maximal stimulation by spermine was observed at the approximate intracellular concentration of Mg2+ (Lundberg et al, 1986;Cochet & Chambaz, 1986).…”
Section: Polyamines and Transportmentioning
confidence: 99%
“…The formation of Ptdlns(4,5)P2, catalysed by the Ptdlns(4)P 5-kinase, is also activated several-fold by polyamines in rat brain or liver plasma membranes (Lundberg et al, 1986(Lundberg et al, , 1987. Interestingly, work with a partially purified rat brain kinase indicated that maximal stimulation by spermine was observed at the approximate intracellular concentration of Mg2+ (Lundberg et al, 1986;Cochet & Chambaz, 1986). The mechanisms of these polyamine effects and their relevance to situations in vivo remain to be established.…”
Section: Polyamines and Transportmentioning
confidence: 99%
“…In particular, polyamine inhibition of phosphoinositidase C activity has been described in permeabilized GH, cells (Wojcikiewicz and Fain, 1988), although other authors have observed enhancements of soluble phosphoinositidase activity by polyamines (Eichberg et al, 1981). Other reported effects of polyamines on the phosphoinositide system include the activation of MODULA TION OF PHOSPffOINOSITIDE HYDROLYSIS 611 phosphoinositide kinases, thereby increasing the radiolabelling of phosphatidylinositol mono-and bisphosphates (Lundberg et al, 1986;Vogel and Hoppe, 1986;Smith and Snyderman, 1988;Wojcikiewicz and Fain, 1988), the inhibition of phosphatidylinosi-to1 bisphosphate phosphatase (Smith and Snyderman, 1988), the activation of inositol 1,4,5-trisphosphate phosphatase (Seyfred et al, 1984), and the inhibition of phorbol ester activation of protein kinase C (Thams et al, 1986).…”
mentioning
confidence: 99%